ANALYSIS OF THE EFFECTIVENESS OF FOLLOW-UP AUDIT RESULTS ON FINANCIAL MANAGEMENT OF THE SOUTH SULAWESI PROVINCE GOVERNMENT - Fera Amelia Putri; Zauhar Qalbi; A. Nurul Fatima Zahra; Dwi Yanti; Muh Alfa Reza Malik (RADJA PUBLIKA, 2025)
This study aims to analyze the trend in the effectiveness of follow-up to audit results in the financial management of the South Sulawesi Provincial Government from 2020 to 2023. The method used is a qualitative documentation method utilizing secondary data from the Supreme Audit Agency (BPK) audit report, the South Sulawesi Provincial Government financial report, and the BPK audit opinion report. The analysis was conducted descriptively by comparing changes in audit opinion and the effectiveness of the implementation of recommendations each year. The findings of this study indicate that although the audit opinion has increased from qualified to unqualified, follow-up to the audit results has not reached an optimal level. The large number of recommendations that have not been implemented properly indicates weaknesses in the internal control system and regional asset management. Therefore, increased commitment, human resource capacity development, and improvements in the supervisory system are needed to make regional financial management more transparent and accountable.